ACCOUNTABILITY ANALYSIS OF FINANCIAL MANAGEMENT OF FUND ALLOCATION IN PASANGKAYU VILLAGE - Alfarizi, Muh Agung; Paranon, Selmita (Penelitian dan Pengembangan Ilmu, 2025)
This research focuses on the accountability system, which is a form of accountability for the management of Pasangkayu Village funds by the Pasangkayu Regency government which is carried out starting from the planning, implementation, accountability, and supervision stages of the management of Pasangkayu village funds. The purpose of this study was to determine and analyze the accountability of the Pasangkayu village government in reporting and using the Pasangkayu village allocation fund. This research was conducted because the amount of funds budgeted by the government is vulnerable to fraud due to a lack of transparency in reporting to the public. The type of research used is qualitative research with a descriptive analysis approach. The data collection techniques used are interviews, observation, and documentation. Urban village funds are funds that come from the APBD and APBN which are included in the General Allocation Fund Post (DAU) and the General Transfer Fund. The General Allocation Fund (DAU) is a fund sourced from APBN revenue allocated with the aim of equalizing financial capacity between regions to fund regional needs in the context of implementing decentralization. While the General transfer fund comes from the APBD for shopping and development and purchasing urban village office equipment. The results of the study indicate that Pasangkayu Village is in accordance and in line with Permendagri No. 20 of 2018 from the planning, implementation, management, reporting, and accountability stages and Pasangkayu Regency Regional Regulation Number 5 of 2022 concerning Regional Budget Revenue and Expenditure.